The Effect of Internal Control Systems and Accounting Information Systems on the Quality of Financial Statements PT. Gudang Garam, Tbk and PT. Wilmar Group - Yusuf Faisal; Annisa Rahayu Yulivianti; Suci Dwi Rindiani (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2023)
This research aims to explain how the influence of Internal Control Systems and Accounting Information Systems on the Quality of Financial Statements. Quantitative method used in this research. The population in this study is PT Gudang Garam Tbk and PT Wilmar Group. The sampling technique using a purposive sampling technique was taken based on the criteria for obtaining it, meaning that the information obtained was based on predetermined criteria, namely the finance and accounting departments. The sample of this research is 37 respondents. Methods of data collection using the survey method, namely the authors disseminate directly to the respondents. Data analysis techniques in this study used descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. this study found that there is a positive insignificant effect between the Internal Control System on the Quality of Financial Statements There is a significant positive impact between accounting information systems and the quality of financial statements.